Hospitalization, Asthma Phenotypes, and Readmission Rates in Pre-school Asthma - Donath, Helena; Kluge, Sven; Sideri, Georgia; Trischler, Jordis; Jerkic, Silivija P.; Schulze, Johannes; Zielen, Stefan; Blumchen, Katharina (Frontiers in Pediatrics, 2020)
Objective: Children with preschool asthma suffer disproportionally more often from severe asthma exacerbations with emergency visits and hospital admissions compared to school children. Despite this high disease burden, there are only a few reports looking at this particular severe asthma cohort. Similarly, there is little real-life research on the distribution of asthma phenotypes and personalized treatment at discharge in this age group. Patients and Methods: Retrospective analysis of the electronic charts of all children aged 1-5 years with asthma hospitalizations (ICD J45) at the Frankfurt University between 2008 and 2017. An acute severe asthma exacerbation was defined as dyspnea, oxygen demand and / or systemic steroid therapy. Age, gender, duration of hospitalization, asthma phenotype, treatment and readmission rate were analyzed. Results: Of 572 patients, 205 met the definition of acute severe asthma. The phenotypic characterization showed 56.1% had allergic asthma, 15.2 % eosinophilic asthma and 28.7% non-allergic asthma. Of these patients, 71.7% were discharged with inhaled corticosteroids (ICS) or ICS + long-acting-beta-agonists (LABA), 15.1% with leukotriene antagonists (LTRA) and 7.3% salbutamol on demand. The rate of emergency presentations (emergency department and readmission) within 12 months after discharge was high (n = 42; 20.5%). No phenotype tailored treatment was detectable. Neither the number of eosinophils (> 300/ µl) nor the treatment at discharge had an effect on emergency visits and readmission rate. Conclusion: Despite protective therapy with ICS, ICS + LABA or LTRA, the readmission rate was high. Thus, current care and treatment strategies should be reevaluated continuously, in order to better control asthma in preschool children and prevent hospitalization.